2011
DOI: 10.1093/nar/gkr242
|View full text |Cite
|
Sign up to set email alerts
|

Native homing endonucleases can target conserved genes in humans and in animal models

Abstract: In recent years, both homing endonucleases (HEases) and zinc-finger nucleases (ZFNs) have been engineered and selected for the targeting of desired human loci for gene therapy. However, enzyme engineering is lengthy and expensive and the off-target effect of the manufactured endonucleases is difficult to predict. Moreover, enzymes selected to cleave a human DNA locus may not cleave the homologous locus in the genome of animal models because of sequence divergence, thus hampering attempts to assess the in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…The concept of tapping the reservoir of natural diversity within the LHE family has been recently described (42) as an attractive alternative to extensive protein engineering. In that study, the tendency of LHEs (in particular, those associated with inteins) to tolerate base substitutions in their DNA target sites that correspond to degenerate or "wobble" positions in their host genes (which lead to synonymous or neutral mutations in the host gene product) was documented.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of tapping the reservoir of natural diversity within the LHE family has been recently described (42) as an attractive alternative to extensive protein engineering. In that study, the tendency of LHEs (in particular, those associated with inteins) to tolerate base substitutions in their DNA target sites that correspond to degenerate or "wobble" positions in their host genes (which lead to synonymous or neutral mutations in the host gene product) was documented.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other targeted endonuclease platforms, HEs use a single protein domain for target site binding and cleavage, and it was suggested that any off-target activity would be more limited and predictable because potential off-target sites need to be substrates for both binding and cleavage. Although off-target cleavage by HEs can been observed (Barzel et al 2011), the levels seen depend on the particular HE and in general tend to be low. Subsequently, newer HE platforms have been developed that increase enzyme specificity, and subsequently the levels of HE-mediated off-target cleavage can be significantly minimized (Boissel et al 2014; Wolfs et al 2014).…”
Section: Hurdles To Human Applicationmentioning
confidence: 99%
“…To date, hundreds of HEs have been identified in Archaea, Eubacteria and Eukarya and their viruses (Barzel et al ., 2011). HEs are classified into five families based on their conserved active site core motif.…”
Section: Rare-cutting Endonucleases Natural and Engineeredmentioning
confidence: 99%
“…To take advantage of the reservoir of natural diversity, the enormous public sequence databases were searched to create a library containing an estimated 416 unique target ranges for 684 HEs that can be freely accessed at http://homebase-search.tau.ac.il/ (Barzel et al ., 2011). Structural conservation permits well-studied HEs to serve as scaffolds onto which specificity determinants identified in such libraries may be grafted, thereby generating novel specificities.…”
Section: Rare-cutting Endonucleases Natural and Engineeredmentioning
confidence: 99%